Nomads in south-eastern Moldova and the Balkans in the 16th–17th centuries - Chirtoagă, Ion; Chirtoagă, Valentina (Balcanica Posnaniensia. Acta et studia, 2007)
The aim of this article is to characterise the migration and settlement processes of nomadic tribes (with particular reference to the Tatar Nogais) in the area between the Prut, Dniester and Black Sea, and to explain their role in Ottoman politics. Particular attention is paid to the emergence of Budjak – a border and transition region where tribes such as the Orumbetoglu and Oracoglu have settled since the 16th century. The research is based on Ottoman documents, chronicles of Turkish and Romanian origin, diplomatic correspondence and research by historians such as D. Cantemir and N. Iorga. On this basis, the author examined the dynamics of nomadic migration and its relations with the local population. The research shows that the nomads were used by the Ottomans as auxiliary troops and as an instrument of political control and economic exploitation. In the 17th century, Budziak transformed from a narrow coastal strip on the Black Sea into a wider border area. The nomads played a key role there and at the same time influenced the Ottoman policy towards neighbouring states.